Examination of tissue temperature profile during photothermal interaction of laser irradiation - Köseoğlu, Muhammed Hakan. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2007., 2007)
During laser surgery, temperature measurement is critical in order to know the photothermal effect of laser irradiation on tissue. Depending on the duration and peak value of the temperature achieved, different tissue responses take place such as coagulation, vaporization, melting and carbonization. There are extensive studies about photothermal effects of laser tissue interaction. In all these studies, measuring temperature accurately is the essential part. Different methods are available for measuring tissue temperature resulting from absorption of laser energy. For deep measurement, temperature sensing probes are the most commonly used devices in biomedical applications. In this study, the temperature values at different radial and axial distances were measured during laser (980nm diode laser) irradiation from different types of tissues (lamb kidney, heart and brain). Moreover, the effects of different power levels (2W, 3W, 4W) and different distances from target point on tissue temperature changes were compared. Thermocouple was used as temperature measuring device during laser irradiation. The deviations in the measurement of direct absorption of laser energy by thermocouple needles were taken into account. As a result of the experiments, it was observed that temperature increases are linearly positively correlated with the laser power levels and, the temperature decreases exponentially as the distance from the target point of laser light increases.|Keywords: Laser-tissue interaction, 980-nm diode laser, photo-thermal effect, thermocouple.